CHARACTERISTICS OF THE TRUNKS OF SCOTS PINE (PINUS SYLVESTRIS) FOR PRODUCTION OF SOLID WOOD MATERIALS (Innovation in Woodworking Industry and Engineering design, 2026)
The results from the studies on the dimensional and qualitative characteristics of model trunks of Scots pine have been presented in this report. The following dimensional characteristics: diameter, length and taper have been determined. The presence, type and dimensions of knots on the outer surface of the tree trunks and inside the wood have been determined. The presence of decay, spiral grain and other defects of wood and trunk shape have been established. The results have been analysed and relations to the existing standards, possible application of wood and requirements to the solid wood materials have been made. Relevant methods and techniques for efficient processing have been suggested.